Recognition of prior learning (RPL) policy in Australian higher education: the dynamics of position-taking - Pitman, Tim; Vidovich, L. (Routledge, 2012)
The Bourdieuian concept of ‘position-taking’ is applied in this analysis of recognitionof prior learning (RPL) policy and practice in Australian higher education.Data from institutional documents and participant interviews indicate that,within RPL policy, the universities selectively employ prevailing discourses of‘quality’ and ‘equity’ to reinforce or potentially improve their reputation andsymbolic power in the !eld of higher education. There is no common consensusabout either equity or quality across the sector, as each university interprets thetwo concepts for its own bene!t. The evidence suggests that, despite rhetoric ingovernment policy implying that both are equally important, quality is a farstronger discourse and policy imperative than equity in RPL policy and practice.Also, RPL policies and practices provide an insight into how the key policy prioritiesof equity and quality are addressed by universities, when applied to aspeci!c educational process or practice.